(untitled) (Medico Legal Update, 2020)
Trichomoniasis is a sexual transmitted disease that affects human fertility. In women, trichomoniasis has been related to infertility due to pelvic inflammatory disease that compromises tubal patency, while in men, trichomoniasis may contributed to infertility by deficit of sperm cell quality and function due to physical damage. In this article, asymptomatic fifty couples with unexplained infertility, undergoing In Vitro Fertilization (IVF) were examined for Trichomonas vaginalis (T.V.) infection. In 70% of couples, embryo implantation failed and pregnancy was not achieved, probably as a consequence of trichomoniasis. The result indicates that T. vaginalis pathogenicity, adverse reproductive health outcomes, in time diagnosis, and treatment may improve implantation rate in patients with unexplained infertility undergoing Assisted reproductive technology ( ART).